PROTECTION ON FREEDOM OF THE PRESS FOR FOREIGN JOURNALISTS AND JOURNALISTIC VISA IN INDONESIA - Fianka Aiza; Lena Farsia (Student Journal of International Law, 2021)
This study analyses how Indonesia enforces the law to protect the freedom of the press for foreign journalists and imposes strict visa regulations on them. The method used to conduct this research is the normative legal method. This study shows that Indonesia upholds human rights such as freedom of expression, but there are no specific legal rules to uphold such rights over foreign journalists. Rules are only available on the enactment of a journalistic visa. Therefore, it is recommended for Indonesia's Lawmakers to compose a new Law to uphold the rights and obligations of foreign journalists while they are in Indonesia and develop a monitoring body for foreign journalists so that Indonesia can ensure the protection of freedom of the press and the national security. Keywords: Foreign journalists; Freedom of Press; Journalistic Visa.